The When and Where: How development modulates immunity through a miRNA-NLR-phasiRNA network - Del Espino Pérez, Ángel; López-Márquez, Diego; López-Pagán, Nieves; Rubio-Somoza, Ignacio; Ruiz-Albert, Francisco Javier; Rodríguez-Bejarano, Eduardo; Beuzón-López, Carmen del Rosario (My University, 2022)
Plants possess a battery of dedicated intracellular immune receptors known as nucleotide-binding leucine-rich repeat proteins (NLRs) involved in recognition of pathogen-derived effectors and activation of effector-triggered immunity (ETI). In a recent work, we report a two-tiered regulatory network in Arabidopsis mediated by a microRNA (miR825-5p) and a wave of secondary NLR-derived phased small RNAs (phasi-NLRs) involved in silencing dozens of NLR genes encoding Toll/interleukin-1 NLRs (TNLs). In our model, targeting of MIST1 (microRNA-silenced TNL1) transcripts by miR825-5p, triggers the generation of phasi-NLRs that subsequently silence a wide network of TNL-encoding genes and reinforce the silencing of MIST1. Current knowledge regarding how these networks are modulated contribute to immunity during different developmental stages is scarce. Through generation of GUS-based A. thaliana reporter lines we have characterized the expression pattern of both MIR825 and MIST1 genes and the domain activity of miR825-5p. A comprehensive analysis of RNA and small RNA-seq datasets, unravelled a hitherto unknown connection between miR825-5p/phasi-NLR mediated regulation of NLRs and plant development. Further analysis supports the notion that the action of this regulatory mechanism is restricted to control NLR expression in leaves. We are working to understand how the changes on miRNA/phasi-NLR levels during developmental stages modulate the immune response and the biological impact of this developmental-dependent regulation on plant health. Our results point to a developmentally regulated sRNA-based control of NLR expression in Arabidopsis and shed light on how levels of these regulatory molecules (miRNAs and phasi-NLRs) are modulated during development or in an organ specific manner to fine-tune NLR expression.
Keywords: Plantas - Defensas - Congresos; Plantas - Enfermedades y plagas - Congresos; Plantas - Mejora genética - Congresos; Defensa; Planta; Regulación génica; miRNA defensa plantas regulación resistencia